Latitudinal variation in ambient UV-B radiation is an important determinant of Lolium perenne forage production, quality, and digestibility - Comont, David (Oxford University Press, 2013)
Few studies to date have considered the responses of agriculturally important forage grasses to UV-B radiation. Yet grasses such as Lolium perenne have a wide current distribution, representing exposure to a significant variation in ambient UV-B. The current study investigated the responses of L. perenne (cv. AberDart) to a simulated latitudinal gradient of UV-B exposure, representing biologically effective UV-B doses at simulated 70, 60, 50, 40, and 30° N latitudes. Aspects of growth, soluble compounds, and digestibility were assessed, and results are discussed in relation to UV-B effects on forage properties and the implications for livestock and bio-ethanol production. Aboveground biomass production was reduced by approximately 12.67% with every 1 kJ m–2 day–1 increase in biologically weighted UV-B. As a result, plants grown in the highest UV-B treatment had a total biomass of just 13.7% of controls. Total flavonoids were increased by approximately 76% by all UV-B treatments, while hydroxycinnamic acids increased in proportion to the UV-B dose. Conversely, the digestibility of the aboveground biomass and concentrations of soluble fructans were reduced by UV-B exposure, although soluble sucrose, glucose, and fructose concentrations were unaffected. These results highlight the capacity for UV-B to directly affect forage productivity and chemistry, with negative consequences for digestibility and bioethanol production. Results emphasize the need for future development and distribution of L. perenne varieties to take UV-B irradiance into consideration.